Prevalence of Chronic Periodontitis in Patients with Esophageal, Gastric, and Colorectal Cancer - Delaram Poorkazemi; Pegah Nasiri; Ali Malekzadeh Shafaroudi; Ghasem Janbabai; Mahmood Moosazadeh; Javad Mehrani Sabet (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Systemic conditions, such as diabetes or cardiovascular disease are associated with periodontal disease. Recent studies suggested a link between periodontitis and gastrointestinal cancers. Due to the importance of this issue, this study aimed to evaluate the prevalence of chronic periodontitis in patients suffering from gastric, esophageal, and colorectal cancers attending Sari Imam Khomeini Hospital, 2017-2018. Materials and methods: In this cross-sectional study, clinical examination of 100 patients was performed by assessing clinical attachment loss (CAL), bleeding on probing (BOP), and tooth loss. After recording the periodontal pockets' depth and gingival recession, the CAL was calculated. Chronic periodontitis was categorized as mild, moderate, and severe based on classification of periodontal disease. Chi-Square and ANOVA were applied for data analysis. Results: According to findings in patients with gastric cancer (n= 23) mild, moderate and sever periodontitis were seen in 8.7%, 26.1%, and 26.1%, respectively. There were 10 patients with esophageal cancer of whom 40% were healthy, 40% had moderate periodontitis, and 20% had severe periodontitis. Among patients with colorectal cancer (n=67), 7.5% had mild periodontitis, 46.3% had moderate periodontitis, and 1.5% had severe periodontitis. Conclusion: In patients with moderate to severe chronic periodontitis, due to the loss of periodontal support of the teeth that leads to loosening the teeth, the chances of tooth loss increase which naturally disrupts the patient's eating process and causes digestive problems.